السياسة الطاقوية في الجزائر وانعكاسها على التنمية المستدامة - بلاطش حسيبة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تزخر الجزائر بإمكانات هائلة من مصادر الطاقة المتجددة وغير المتجددة، التي تطمح لتطويرها واستغلالها بما يتماشى ومختلف المتغيرات الاقتصادية المحلية والدولية، وذلك من خلال تحديد عدّة ركائز وأسس لسياستها الطاقوية، وتهدف هاته الورقة البحثية إلى التركيز على تحليل انعكاسات التوجهات العامة للسياسة الطاقوية الجزائرية من خلال إستراتيجية "آفاق 2030" على التنمية المستدامة، ومحاولة حصر أهم الأطر القانونية والتنظيمية التي وضعت من أجل تطوير الاستغلال الأمثل للموارد الطاقوية سواء المتجدّدة أو غير المتجدّدة وذلك باستخدام مدخل الاقتصاد السياسي ومنهج دراسة الحالة، واللّذان توصلنا من خلالها إلى أنّ تحقيق التنمية المستدامة مرهون بالتحرر من قطاع المحروقات والسير بخطى ثابتة ومدروسة نحو الانتقال الطاقوي . Algeria abounds with huge potentials from renewable and non-renewable energy sources that aspire to develop and exploit by defining the foundations and directives of its energy policy, this study aims to analyze the goals, dimensions and repercussions of the general energy and political trends in Algeria through the strategy of using the 2030 Agreement and its impact on sustainable development, and trying to limit the most important legal and regulatory frameworks that were developed for the development and optimization of traditional and non-traditional energy resources using the approach of the political economy and case study, through the late we concluded that achieving sustainable development is subject to liberalization from the hydrocarbon sector and achieving energy transitions.